1989
DOI: 10.1002/j.1460-2075.1989.tb08582.x
|View full text |Cite
|
Sign up to set email alerts
|

Preferential, cooperative binding of DNA topoisomerase II to scaffold-associated regions.

Abstract: DNA elements termed scaffold‐associated regions (SARs) are AT‐rich stretches of several hundred base pairs which are known to bind specifically to nuclear or metaphase scaffolds and are proposed to specify the base of chromatin loops. SARs contain sequences homologous to the DNA topoisomerase II cleavage consensus and this enzyme is known to be the major structural component of the mitotic chromosome scaffold. We find that purified topoisomerase II preferentially binds and aggregates SAR‐containing DNA. This i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
199
0
2

Year Published

1993
1993
1999
1999

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 304 publications
(213 citation statements)
references
References 45 publications
12
199
0
2
Order By: Relevance
“…Besides its enzymatic activity that creates transient double-strand breaks in duplex DNA and passes DNA strands through one another, the protein has been shown to interact with the MAR and SAR elements [8]. Thus, topo 11 is thought to have catalytic as well as structural functions.…”
Section: Introductionmentioning
confidence: 99%
“…Besides its enzymatic activity that creates transient double-strand breaks in duplex DNA and passes DNA strands through one another, the protein has been shown to interact with the MAR and SAR elements [8]. Thus, topo 11 is thought to have catalytic as well as structural functions.…”
Section: Introductionmentioning
confidence: 99%
“…Transient transfections such as these do not represent the physiological scenario where histone proteins and architectural elements of tertiary structure, such as scaffold attachment regions (SARs) are involved. An indicator of an SAR is the presence of AT-rich elements, 35,36 and such a region is located 5Ј of −1025hLuc. It is possible that complex secondary structure resulting from internal homology is formed at this region, preventing TF ingress, and thus transcriptional activation.…”
Section: Discussionmentioning
confidence: 99%
“…Earnshaw et al [11] and Adachi et al [12] indicated that Topoisomerase II is a component of the chromosome scaffold and nuclear matrix. Nakayasu and Berezney [13] identified, with two dimensional IEF/SDS-PAGE and immunobloting, laminins A, B, C, nucleolar protein B23 and some matrins as components of the nuclear matrix in a broad sense.…”
Section: Discussionmentioning
confidence: 99%
“…The main component of nuclear matrix and chromosome scaffold is nonhistone proteins [1][2][3][4], [10]. Although many biochemical and immunocytochemical analyses have been conducted concerning protein composition of the nuclear matrix and chromosome scaffold, only a few proteins (such as topoisomerase II) have been identified [11][12][13][14][15][16]. Some previous biochemical analyses indicated that a polypeptide of about 37 kD, which is equivalent to tropomyosin in molecular weight, existed in the nuclear matrix and chromosome scaffold [15], [17][18][19][20] and this polypeptide might represent tropomyosin [19].…”
Section: Introductionmentioning
confidence: 99%